Aquarelas : a linguagem das cores em Fayga Ostrower - Silva, Wanessa Cordeiro da (2016)
The main objective of this study was to analyze the watercolors produced by Fayga Ostrower at the end of 1990’s. In her art technic, the artist made use of freedom of gestures and shapes. The issue that has permeated this study was to understand how color